DEVELOPMENT OF THE AVI-SENA BOOK : EDUCATIONAL MEDIA FOR THE PREVENTION OF SEXUAL VIOLENCE IN EARLY CHILDHOOD - Dian Furwasyih; Gina Muthia; Ilham Akerda Edyyul; Sunesni Sunesni (Institut Pendidikan Tapanuli Selatan, 2024)
Background: This research aims to develop educational media that are informative, innovative, interactive, and appropriate to early childhood development that discuss reproductive health, sexual education, and efforts to prevent sexual violence in early childhood. This media is named AVI-SENA Book. Methods: This research is Research and Development (RnD) research using 3D development processes or steps that include defining, designing, and developing. Results and Discussion: In the definition stage, this product is defined as an interactive book for early childhood that discusses reproductive health, sexual education, and efforts to prevent sexual violence in early childhood. The book is entitled AVI-SENA. The design stage includes format selection and initial media design. The media was developed using flannel as the basic material, and is made in a busy book or activity book format for early childhood. The third stage is development. This stage includes product creation and expert review. There are two experts involved, namely media experts and material experts. From the results of the expert review, it was found that the product score was in the sufficient category, namely 2.53 for media and 2.47 for material. There are several recommendations from experts that are of concern in improving product quality, namely that the basic material of the media should be replaced with wipe and clean paper because the use of flannel cloth is not recommended, then studying the material in more depth and detail with clearer activity instructions so that children can understand it better and the activities in the book can also be modified so that they are more relevant to the content. Conclusion: AVI-SENA Book was developed as an alternative educational media for preventing sexual violence against children. It is recommended to replace the AVI-SENA manufacturing material with a wipe and clean paper to improve the quality of the media created so that it is more enjoyable for children to participate in activities using the AVI-SENA Book.